Determinants of Price Book Value in the Company Pharmacy 2016–2021 - Sanjaya, Surya (Journal of International Conference Proceedings, 2023)
This study aims to determine whether the influence of the Dividend Payout Ratio, Price Earning Ratio, and Debt to Equity Ratio on Price Book Value in Pharmaceutical sub-sector companies Listed on the Indonesia Stock Exchange (IDX) for the 2016 – 2021 period. This research approach uses an associative approach. The population in this study were 10 companies and the samples in this study were 5 companies. The period is carried out for 6 years, starting from 2016 – 2021. The data used is secondary data, namely the data obtained is in the form of financial reports from site www.idx.co.id. Technis data analysis was performed using statistical analysis, namely: multiple linear analysis, classic assumption test, and hypothesis testing, as well as the coefficient of determination with SPSS 21.0 for windows. The results showed that partially the Dividend Payout Ratio and the Debt to Equity Ratio had a negative and insignificant effect on the Price Book while the Price Earning Ratio had a positive and significant effect on the Price Book Value. Simultaneously the Dividend Payout Ratio, Price Earning Ratio, and Debt to Equity Ratio have a positive and significant influence on the Price Book Value.